Dealing with the Challenges of Capital Inflows in the Context of Macrofinancial Links - Ghosh, Swati R (World Bank, Washington, DC, 2012)
In the wake of the recent global financial crisis, emerging markets have seen a significantly higher degree of volatility in their capital flows. At the onset, all countries experienced sudden stops and increases in risk premia. Following this initial period of uncertainty, financial markets began to differentiate between the countries, and while most developing regions have regained access to both, debt and equity issuance, the pace of recovery of capital inflows has been particularly remarkable for some countries. Given the likelihood that the prevailing low interest rates in the developed world will remain for some time to come, and given the prospects of faster growth in emerging markets, it is likely that some emerging markets will experience significant surges in capital flows in the near future. This note examines potential policy responses to maintain macroeconomic and financial sector stability in the face of increased capital inflows.